A protocol for the first episode psychosis outcome study (FEPOS): ≥15 year follow‐up after treatment at the Early Psychosis Prevention and Intervention Centre, Melbourne, Australia. Issue 7 (20th August 2021) - Cotton, Sue; Filia, Kate; Watson, Amity; Mackinnon, Andrew J.; Hides, Leanne; Gleeson, John F. M.; Berk, Michael; Conus, Philippe; Lambert, Martin; Schimmelmann, Benno; Herrman, Helen; Rayner, Victoria; et al.
Abstract: Background: Specialist early intervention (SEI) service models are designed to treat symptoms, promote social and vocational recovery, prevent relapse, and resource and up‐skill patients and their families. The benefits of SEI over the first few years have been demonstrated. While early recovery can be expected to translate to better long‐term outcomes by analogy with other illnesses, there is limited evidence to support this from follow‐up studies. The current study involves the long‐term follow‐up of a sub‐set of first episode psychosis (FEP) patients, with a range of diagnoses, who were first treated at Orygen's Early Psychosis Prevention and Intervention Centre (EPPIC) between 1998 and 2000. The aim of this paper is to present the methodology for this follow‐up study. Methods: Between January 1998 and December 2000, 786 patients between the ages of 15–29 years were treated at EPPIC, located in Melbourne, Australia. Our cohort consists of 661 people (82 were transferred/discharged and 43 were not diagnosed with a psychotic disorder at time of discharge). The 18‐month treatment characteristics of this cohort have been extensively examined in the First Episode Psychosis Outcome Study (FEPOS). The ≥15 year outcomes of this cohort are being examined in this study, known as FEPOS15. Results: Participant follow‐up is ongoing. In order to extend and assess broader outcomes of the cohort, data linkage with health‐related databases will be conducted. Conclusion: This study will provide a comprehensive evaluation of the long‐term trajectory of psychotic disorders after treatment for FEP in a SEI service.